PENGARUH MINAT KONSUMEN DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PERBAIKAN KAPAL TONGKANG PADA TAHUN 2012 DI PT. BANDAR ABADI BATAM - Dian Novita Sari; Edwin Agung Wibowo; Sriwati Sriwati (BENING, 2014)
The research was conducted in PT. Bandar Abadi Batam. The purpose of this research to determine the effect of customer  interest and the company image of the barge repair decisions, either separately (Partial) or jointly (simultaneously). In this study the authors used a sample of 30 customer. Types of data used are primary data and secondary data. Sources of primary data obtained from questioner’s customer who repair ships at Eternal PT.Bandar Abadi Batam. Secondary data obtained from PT.Bandar Abadi Batam and documents obtained from related literature and can support as well as useful for this research. Data was collected by means of questioner’s. Data were analyzed by descriptive statistics, which are used to describe the picture of the object under study through the medium of a sample or population of data obtained in the field associated with the relevant theories and techniques of quantitative analysis of the data that has been given a score according to the scale of measurement used the Likert scale and to test the results using SPSS ( Statistical Product and Service Solution ) version 20.From the research, the authors conclude that partial Customer Interest (XI) and a significant positive effect on Decision Repair (Y), the test results of 0.123 or 12.3%. While the Company Image (X2) is not positive and not significant effect on decision Repair (Y) with the results of the t test of 0.147 or 14.7%.